Characteristics of Hypertension Patients with Chonic Kidney Disease at Ibnu Sina Hospital, Makassar City Year 2022-2023 - Aulia, Nabila; Kanang, Indah Lestari Daeng; Fattah, Nurfachanti; Hamsah, Pratiwi Nasir; Hasbi, Berry Erida (Jurnal Biologi Tropis, 2024)
Hypertension is a condition where the systole is more than or equal to 140  and the diastole is more than or equal to 90 mmHg. In Indonesia the number of hypertension sufferers reaches 70 million people. The prevalence of hypertension in adults is 6-15%. Hypertension that has been going on for a long time and is not controlled, impacts the blood vessels in the kidneys and causes sclerosis of the blood vessels resulting in glomerular damage and tubular atrophy leading to kidney damage. methods: This is a descriptive study with a cross design sectional Results : Hypertension sufferers with the highest incidence of chronic kidney disease are aged 55-64 years (32.9%), the gender is mostly male (57.6%) while female (424%), with a long history of suffering from hypertension is ≥5 year (63,5%), the highest blood pressure control was found in uncontrolled blood pressure (56.5%), and the use of antihypertensive drugs in the form of CCB drugs (51.8%).Conclusion: Hypertensive patients with the incidence of chronic kidney disease at Ibnu Sina Hospital, Makassar City in 2022-23 are mostly at the age of 55-64 years, male with a long history of suffering from hypertension of 5-10 years and control of uncontrolled blood pressure and use of other types of antihypertensive medication, namely Calcium Channel Blocker (CCB).